Enhancing Financial Literacy and Income Strategies Among College Students Through Community Outreach (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The phenomenon of consumptive debt faced by society today, especially among young people, highlights the   urgent need to improve financial literacy. The use of credit, installments, or loans without careful planning often results in ongoing financial burdens and negatively affects long-term well-being. Therefore, raising awareness about the risks of consumptive debt is crucial as an early preventive measure. This activity began with an educational session on financial management, focusing on the concept of consumptive debt. The next part involved financial planning education in the digital transaction era. Pre-test and post-test questionnaires were administered to assess students’ understanding. The results of the pre-test and post-test Paired-sample t-test results confirmed a statistically significant knowledge gain from pre- to post-intervention, with university students showing an average increase of 10.491 points (t = -10.002, df = 272, p < .001). This positive shift validates the effectiveness of the structured program, further supported by a strong positive correlation between pre- and post-test scores (r = .558, p < .001), indicating consistent assessment reliability demonstrated a significant improvement in students' understanding of financial management and planning in the digital transaction era, including their ability to identify financial risks. The conclusion of this activity is that education on financial management and planning proved to make a significant difference in enhancing students’ understanding, as well as helping them to realize early on the importance of sound financial management.